Pengaruh pembelajaran manajemen keuangan terhadap perilaku berinvestasi yang dimoderasi gender - Masno Marjohan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The purpose of this study was to analyze the effect of learning financial management on investment behavior of Master of Management students at Pamulang University and to determine the effect of learning financial management on investment behavior moderated by gender. This research is an applied research type with a descriptive statistical verification approach. The population is Master of Management students class 2018 and 2019, sampling using purposive sampling so that the number of samples is 100 respondents. Data analysis using path analysis method using SmartPLS program. Data processing techniques using SEM method based on Partial Least Square (PLS). The results showed that there was an effect of financial management learning on investment behavior of Pamulang University Master of Management students, gender variable could not moderate the effect of financial management learning on investment behavior of Pamulang University Master of Management students.